Measuring Research Impact in an Open Access Environment - Scholze, Frank (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
This paper focuses on electronic publication impact as a limited, but rather well defined sub-field of research impact. With Open Access, a much bigger corpus of data has become available for statistical analysis. Publication impact can be measured by author- or reader-generated data. Author-generated data would be citations. Reader-generated data would be usage. Usage data can be collected through webserver or linkresolver logs. It has to be normalized in order to be shared and analysed meaningfully. The paper presents current initiatives and projects aiming to provide a suitable infrastructure, including publisher data (COUNTER/SUSHI) and data collected from Open Access repositories (using OAI-PMH and OpenURL ContextObjects). Citation and usage data can be analyzed quantitatively or structurally. These new metrics can enhance or complement existing metrics like the Journal Impact Factor (JIF). Services like decision support systems for collection management or recommender systems can also be built on this metrics.